ADCP current measurements (38 kHz) during RV SONNE cruise SO292/2 - Walter Menapace; Robert Kopte; Mona Lütjens; Gavin D extquotesingleMello; Meret Felgendreher (PANGAEA, 2023)
Upper-ocean velocities along the cruise track of Sonne cruise SO292/2 were continuously collected by a vessel-mounted Teledyne RD Instruments 38 kHz Ocean Surveyor ADCP. The transducer was located at 6.0 m below the water line. The instrument was operated in narrowband mode with 32 m bins and a blanking distance of 16.0 m, while 50 bins were recorded using a pulse of 2.92 s. Beam velocities as recorded by the data acquistion software VmDas were transformed to ship coordinates and after merging with the navigation and attitude data from the ship extquotesingles gyro and Global Positioning systems into earth coordinates. The ship extquotesingles velocity was calculated from position fixes obtained by the Global Positioning System (GPS). Accuracy of the ADCP velocities mainly depends on the quality of the position fixes and the ship extquotesingles heading data. Further errors stem from a misalignment of the transducer with the ship extquotesingles centerline. Data post-processing included water track calibration of the misalignment angle (-0.22° +/- 1.2887°) and scale factor (1.0040 +/- 0.0299) of the Ocean Surveyor signal. The average interval was set to 120 s. Velocity quality flagging is based on following threshold criteria: abs(UC) or abs(VC) > 1.5 m/s, rms(UC_z) or rms(VC_z) > 0.5.